Microstructure of recycled aggregate concrete - Rao, M. Chakradhara; Bhattacharyya, S.K.; Barai, S.V. (Journal of Structural Engineering, 2024)
In the present study, the effect of recycled coarse aggregate (RCA) obtained from three different demolished old structures on the interfacial transition zone (ITZ) characteristics viz. porosity, hydration compounds and anhydrous cement of recycled aggregate concrete (RAC) were evaluated. RAC mixes are prepared with each source of RCA separately. In order to assess the performance of RAC in comparison with normal concrete, two normal concrete mixes prepared with 100% natural coarse aggregate. Locally available natural sand is used in all mixes. All mixes were designed for M25 grade of concrete in accordance with BIS (IS: 10262-1982) with a free w/c ratio of 0.43. The experimental results reveal that the effect of recycled coarse aggregate on the properties of ITZ was evident that the ITZ in RAC is less dense and more porous than the concrete with natural aggregates.